2013
DOI: 10.1186/1745-6215-14-365
|View full text |Cite
|
Sign up to set email alerts
|

Vancouver At Home: pragmatic randomized trials investigating Housing First for homeless and mentally ill adults

Abstract: BackgroundIndividuals with mental illnesses are overrepresented among the homeless. Housing First (HF) has been shown to promote positive outcomes in this population. However, key questions remain unresolved, including: how to match support services to client needs, the benefits of housing in scattered sites versus single congregate building, and the effectiveness of HF with individuals actively using substances. The present study aimed to recruit two samples of homeless mentally ill participants who differed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(109 citation statements)
references
References 67 publications
0
109
0
Order By: Relevance
“…Significant differences in HQ between groups in Vancouver are likely attributable to the concentration of very low quality accommodations in the city's urban core, where homelessness is most visible. 24,25 After adjustment for other important variables, site was a significant predictor of HQ only for Winnipeg. There are important contextual differences with this city that can explain these findings.…”
Section: Discussionmentioning
confidence: 97%
“…Significant differences in HQ between groups in Vancouver are likely attributable to the concentration of very low quality accommodations in the city's urban core, where homelessness is most visible. 24,25 After adjustment for other important variables, site was a significant predictor of HQ only for Winnipeg. There are important contextual differences with this city that can explain these findings.…”
Section: Discussionmentioning
confidence: 97%
“…From using the data from a large Canadian longitudinal research trial, the At Home/Chez Soi Project, possible associations will be evaluated in this study. The At Home/Chez Soi Project (2009-2013) was conceived to investigate the efficacy of the Housing First model in five Canadian urban settings [32,33]. To date, Housing First is considered (confirmed by the At Home/Chez Soi results [34], to be the best available approach to homelessness [35].…”
Section: Are Substance Use and Mental Illness Associated To An Earliementioning
confidence: 99%
“…It is important to note that the inclusion criterion for the At Home study was that all participants had a mental disorder, diagnosed with an appropriate instrument. The design of the At Home study has been described in depth in other papers [32,33].…”
Section: Are Substance Use and Mental Illness Associated To An Earliementioning
confidence: 99%
See 1 more Smart Citation
“…Primary care physicians have the skills to address these issues. 6 A number of studies have examined housing interventions (such as Housing First) in homeless people with mental health disorders and HIV, [7][8][9][10][11] but studies in those with medical disorders have not been reported. In 2010, a GP-led and nurse-led intervention involving a hospital 'in reach' team for homeless people at University College Hospital London was developed.…”
Section: Introductionmentioning
confidence: 99%